Antishadowing Effect on Charmonium Production at a Fixed-Target Experiment Using LHC Beams - Kai Zhou; Zhengyu Chen; Pengfei Zhuang (Advances in High Energy Physics)
We investigate charmonium production in Pb + Pb collisions at LHC beam energy Elab=2.76A TeV at fixed-target experiment (sNN = 72 GeV). In the frame of a transport approach including cold and hot nuclear matter effects on charmonium evolution, we focus on the antishadowing effect on the nuclear modification factors RAA and rAA for the J/ψ yield and transverse momentum. The yield is more suppressed at less forward rapidity (ylab≃2) than that at very forward rapidity (ylab≃4) due to the shadowing and antishadowing in different rapidity bins.